Respuesta :
The simplified form of the expression is a^9^6
Given the indices expression
- [tex](\frac{a^{-8}b}{a^{-5}b^3} )^ {-3}[/tex]
Using the laws of indices given as:
[tex]a^m \times a^n = a^{m+n}\\\frac{a^m }{a^n} = a^{m-n}\\(a^m)^n = a^{mn[/tex]
Applying this law on the expression, we will have:
[tex]=(a^{-8-(-5)}b^{1-3})^{-3}\\=(a^{-8+5}b^{-2})^{-3}\\=(a^{-3}b^{-2})^{-3}\\=a^9b^6[/tex]
Hence the simplified form of the expression is a^9^6
Learn more on indices here: https://brainly.com/question/8952483